Modification of Nafion® Membrane via a Sol-Gel Route for Vanadium Redox Flow Energy Storage Battery Applications - Shu-Ling Huang; Hsin-Fu Yu; Yung-Sheng Lin (Journal of Chemistry)
Nafion 117(N-117)/SiO2-SO3H modified membranes were prepared using the 3-Mercaptopropyltrimethoxysilane (MPTMS) to react with H2O2 via in situ sol-gel route. Basic properties including water uptake, contact angle, ion exchange capacity (IEC), vanadium ion permeability, impedance, and conductivity were measured to investigate how they affect the charge-discharge characteristics of a cell. Furthermore, we also set a vanadium redox flow energy battery (VRFB) single cell by the unmodified/modified N-117 membranes as a separated membrane to test its charge/discharge performance and compare the relations among the impedance and efficiency. The results show that the appropriate amount of SiO2-SO3H led into the N-117 membrane contributive to the improvement of proton conductivity and vanadium ion selectivity. The permeability was effectively decreased from original 3.13 × 10−6 cm2/min for unmodified N-117 to 0.13 × 10−6 cm2/min for modified membrane. The IEC was raised from original 0.99 mmol/g to 1.24 mmol/g. The modified membrane showed a good cell performance in the VRFB charge/discharge experiment, and the maximum coulombic efficiency was up to 94%, and energy efficiency was 82%. In comparison with unmodified N-117, the energy efficiency of modified membrane had increased more than around 10%.